Hybrid Deliberation in the Dago Elos Urban Land Conflict: Counter-Publics and Communication Strategies - Muklis Efendi; Radita Gora Tayibnafis; Ana Kuswanti (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
This study analyzes deliberative communication practices in urban land conflict, focusing on how communities build and maintain deliberative spaces under structural constraints. A qualitative case study was conducted on the Dago Elos land conflict in Bandung City, involving 331 families facing eviction claims. Data were collected through in-depth interviews with four stakeholder representatives: community leaders, legal aid organizations, local government officials, and land administration agencies. The study reveals three key findings: (1) Institutional fragmentation creates a complete absence of formal dialogue forums between communities and government, forcing communities to develop alternative communication strategies; (2) Counter-public sphere innovation through the Forum Dago Melawan demonstrates successful implementation of deliberative principles (equal participation, consensus-building, reason-giving) at the grassroots level, functioning as a genuine democratic laboratory; (3) Hybrid communication strategies emerge as communities combine rational argumentation with mass mobilization, challenging the traditional dichotomy between reasoned deliberation and political action. Mass actions prove effective in forcing institutional responses when formal channels remain closed, demonstrating that collective mobilization can function as deliberative communication under non-ideal conditions. The research expands deliberative communication theory by showing that deliberative principles can function in non-ideal conditions through creative adaptation and grassroots institutional innovation. Counter-public spheres like Forum Dago Melawan can successfully implement Habermas's ideal speech situation in local settings, while hybrid strategies combining reason-giving with collective action create communicative power capable of influencing administrative responses despite structural power asymmetries. These findings suggest that genuine deliberative communication requires acknowledging and addressing power inequalities rather than hiding them behind claims of procedural neutrality.